Akkermansia muciniphila Exerts Lipid‐Lowering and Immunomodulatory Effects without Affecting Neointima Formation in Hyperlipidemic APOE*3‐Leiden.CETP Mice. Issue 15 (16th August 2019) - Katiraei, Saeed; de Vries, Margreet R.; Costain, Alice H.; Thiem, Kathrin; Hoving, Lisa R.; van Diepen, Janna A.; Smits, Hermelijn H.; Bouter, Kristien E.; Rensen, Patrick C. N.; Quax, Paul H. A.; Nieuwdorp, Max; Netea, Mihai G.; et al.
Abstract : Scope: Akkermansia muciniphila (A. muciniphila) is an intestinal commensal with anti‐inflammatory properties both in the intestine and other organs. The aim is to investigate the effects of oral administration of A. muciniphila on lipid metabolism, immunity, and cuff‐induced neointima formation in hyperlipidemic APOE*3‐Leiden (E3L).CETP mice. Methods and results: Hyperlipidemic male E3L.CETP mice are daily treated with 2 × 10 8 CFU A. muciniphila by oral gavage for 4 weeks and the effects are determined on plasma lipid levels, immune parameters, and cuff‐induced neointima formation and composition. A. muciniphila administration lowers body weight and plasma total cholesterol and triglycerides levels. A. muciniphila influences the immune cell composition in mesenteric lymph nodes, as evident from an increased total B cell population, while reducing the total T cell and neutrophil populations. Importantly, A. muciniphila reduces the expression of the activation markers MHCII on dendritic cells and CD86 on B cells. A. muciniphila also increases whole blood ex vivo lipopolysaccharide‐stimulated IL‐10 release. Finally, although treatment with A. muciniphila improves lipid metabolism and immunity, it does not affect neointima formation or composition. Conclusions: Four weeks of treatment with A. muciniphila exerts lipid‐lowering and immunomodulatory effects, which are insufficient to inhibit neointima formation in hyperlipidemic E3L.CETP mice. Abstract : A. muciniphila administration lowers plasma total cholesterol (A) and triglycerides levels (B) and influences the immune cell composition in mesenteric lymph nodes. Importantly, A. muciniphila reduces expression of activation markers MHCII on dendritic cells and CD86 on B cells. Although treatment with A. muciniphila improves lipid metabolism and immunity, it does not affect neointima formation or composition (C and D).